2012
DOI: 10.1002/ptr.4683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sinensetin on Lipid Metabolism in Mature 3T3‐L1 Adipocytes

Abstract: Sinensetin is a rare polymethoxylated flavone found in certain citrus fruits. In this study, we investigated the effects of sinensetin on lipid metabolism in mature 3T3-L1 adipocytes. Sinensetin decreased the expression of sterol regulatory element-binding protein 1c (SREBP1c), suggesting its antiadipogeneic property via downreguation of SREBP1c. Also, sinensetin increased the phosphorylation of protein kinase A and hormone-sensitive lipase, indicating its lipolytic property via a cAMP-mediated signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Instead, studies on human subcutaneous fat cells have been shown that synephrine has a lypolitic action . A recent study, conducted on 3T3‐L1 cells, demonstrated an antiadipogenetic effect of CA extracts, downregulating C/EBPβ through inhibition of Akt phosphorylation , therefore, preventing the expression of forkhead transcription factor Foxo1 (FKHR) . The main role of Foxo1 is to block adipocytes differentiation, thus, the final consequence of Akt inactivation CA‐mediated is to inhibit PPARγ and C/EBPα expression .…”
Section: Nutraceuticals Targeting Adipocyte Life Cyclementioning
confidence: 99%
“…Instead, studies on human subcutaneous fat cells have been shown that synephrine has a lypolitic action . A recent study, conducted on 3T3‐L1 cells, demonstrated an antiadipogenetic effect of CA extracts, downregulating C/EBPβ through inhibition of Akt phosphorylation , therefore, preventing the expression of forkhead transcription factor Foxo1 (FKHR) . The main role of Foxo1 is to block adipocytes differentiation, thus, the final consequence of Akt inactivation CA‐mediated is to inhibit PPARγ and C/EBPα expression .…”
Section: Nutraceuticals Targeting Adipocyte Life Cyclementioning
confidence: 99%
“…18) Sinensetin significantly and dose-dependently increased cAMP levels at 30 min after treatment (Fig. 5B).…”
Section: Signals At An Early Stagementioning
confidence: 83%
“…We have recently reported that sinensetin had an anti-inflammatory effect in lipopolysaccharide-stimulated RAW 264.7 cells, 17) and it enhanced fatty acid β-oxidation in mature 3T3-L1 adipocytes. 18) In the present study, we investigated the effects of sinensetin on adipogenesis in 3T3-L1 preadipocytes and lipolysis in mature 3T3-L1 adipocytes, and characterized the underlying molecular mechanisms.…”
mentioning
confidence: 99%
“…AMPK activity modulates numerous aspects of the mammalian cell metabolism, and it also has diverse roles that extend from energy metabolism through to transcriptional control. In addition, AMPK functions modulate fatty acid oxidation, glycolysis, fatty acid and cholesterol synthesis (20,21). In order to investigate whether WEP regulates adipogenesis in differentiated 3T3-L1 adipocytes, the effects of WEP on the phosphorylation of AMPK were investigated.…”
Section: Discussionmentioning
confidence: 99%